2006
DOI: 10.1243/09544100jaero66
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of a non-isothermal three-dimensional mixing layer created by a scarfed lobed mixer

Abstract: • This is an article from the journal, Proceedings of the Institution of Me- Abstract: The work presented here considers the complex mixing processes associated with a three-dimensional non-isothermal convoluted mixing layer such as produced by scarfed lobed mixers as used in aero-engine gas turbine exhaust ducts. Numerical simulations of the compressible Navier -Stokes equations in Reynolds-averaged form with a k -1 turbulence model are conducted. The discretization of the high-Reynolds-number form of the k-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…They also reported lower losses for scalloped mixers, compared with other configurations, possibly due to their lowest wetted surface area within the penetration region. Salman et al [24] made a computation for prediction of a nonisothermal three-dimensional mixing layer created by a scarfed lobed mixer. Results showed that the scarfed mixer introduced strong flow asymmetries in the azimuthal direction.…”
Section: Introductionmentioning
confidence: 99%
“…They also reported lower losses for scalloped mixers, compared with other configurations, possibly due to their lowest wetted surface area within the penetration region. Salman et al [24] made a computation for prediction of a nonisothermal three-dimensional mixing layer created by a scarfed lobed mixer. Results showed that the scarfed mixer introduced strong flow asymmetries in the azimuthal direction.…”
Section: Introductionmentioning
confidence: 99%